2008
DOI: 10.1186/1742-4690-5-66
|View full text |Cite
|
Sign up to set email alerts
|

Oral keratinocytes support non-replicative infection and transfer of harbored HIV-1 to permissive cells

Abstract: Background: Oral keratinocytes on the mucosal surface are frequently exposed to HIV-1 through contact with infected sexual partners or nursing mothers. To determine the plausibility that oral keratinocytes are primary targets of HIV-1, we tested the hypothesis that HIV-1 infects oral keratinocytes in a restricted manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
50
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(59 citation statements)
references
References 70 publications
6
50
0
Order By: Relevance
“…The 50% tissue culture infective dose (TCID 50 ) was determined as previously described (10). Briefly, 4 replicates each of cell-associated virus (starting with 200,000 cells/well) and cell-free virus (starting with concentrated virus) were added to the first column of a 96-well plate.…”
Section: Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…The 50% tissue culture infective dose (TCID 50 ) was determined as previously described (10). Briefly, 4 replicates each of cell-associated virus (starting with 200,000 cells/well) and cell-free virus (starting with concentrated virus) were added to the first column of a 96-well plate.…”
Section: Virusesmentioning
confidence: 99%
“…Forty-eight hours after infection, cells were fixed and stained for ␤-galactosidase expression using X-Gal (5-bromo-4-chloro-3-indolyl-␤-D-galactopyranoside; ␤-galactosidase reporter gene staining kit, Sigma-Aldrich) as a substrate. A positive well was defined as one that contained 2 or more blue cells (10). The TCID 50 was calculated using the Spearman-Kaerber formula (11).…”
Section: Virusesmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16] Other studies revealed that direct contact of HIV-1 with the endothelium, which share tight junction structures in common with the epithelium, [17][18][19] could lead to the disruption of endothelial integrity and subsequent increased viral leakage across the endothelium. HIV-1 gp120 and Tat protein have been associated with the disruption of tight junctions in the endothelium.…”
mentioning
confidence: 99%
“…5,6 Significant clinical exposures would require that HIV-1 survive the antiviral activity of saliva and remain infectious within the epithelial cells. We hypothesized, therefore, that HIV-1 escapes inactivation by saliva via rapid uptake into oral epithelial cells.…”
mentioning
confidence: 99%
“…[4][5][6] In the oral cavity, antigen receptive dendritic cells are remote from the mucosal surface, localized to the basal and suprabasal epithelial layers. 14,15 Unlike the vaginal epithelium, 16 the oral intraepithelial dendritic cells (Langerhans cells) do not appear to sample antigen nor capture HIV-1 at the mucosal surface.…”
mentioning
confidence: 99%